Assessing the impact of a serious game on proenvironmental determinants among public administration employees - Daniela ACQUADRO MARAN; Adelina BRIZIO; Alessandra BIANCO PREVOT; Arianna BOLDI; Silvia STANCHI; Manuela REPETTO (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: Objective: To investigate the effectiveness of a serious game based on the Digital Escape Room (DER) in promoting pro-environmental behaviors (PEB) in employees working in a public administration, in the Northwest part of Italy. The study is cast in the framework of the Theory of Planned Behavior (TPB) model, and it integrates emotional and ethical dimensions. Method: DERs on waste prevention and management were administered to 82 employees (53.8 % female). Participants were divided into small teams to maximise participation and collaboration. Based on the literature, a questionnaire was developed to assess PEB and pro-environmental attitude (ATT), emotional intelligence (EI) and environmental ethics (EE) and the effectiveness of DERs on these variables. Results: Findings indicate a significant increase in PEB. An increase is also observed in attitudes towards pro-environmental behavior (ATT), emotional intelligence (EI) and environmental ethics (EE), but not in subjective norms (SN) and perceived control (CON). Discussion: the gaming experience may favor a slight pro-environmental activation. The integration of emotional and moral factors into the TPB model can enhance the predictive capacity of proenvironmental behavior. The experiential and immersive elements of DERs can stimulate personal reflection, emotions and moral values. However, subjective norm (SN) and perceived control (CON) variables were not significantly altered. The playful experience, while effective at an individual level, does not directly impact dimensions that may require structured organizational interventions.